DESAIN DAN IMPLEMENTASI SISTEM INFORMASI PENILAIAN KELULUSAN TERBAIK SISWA MENGGUNAKAN METODE SAW - Hermanto Hermanto; Muhammad Tanwirul Fikri; Muhammad Hafidz Yusuf; Ade Hendi (Jurnal Ilmiah Informatika, 2025)
Graduation is a formal statement issued by an educational institution as proof that students have completed the required academic program. MI Hayatul Wathon, as one of the primary education institutions, aims to produce high-quality graduates. However, the school has not yet implemented a systematic process for determining the best graduates, resulting in the inability to identify outstanding students accurately. Moreover, the announcement of graduation results is still conducted manually by inviting students to the school, which is considered less efficient. This study presents the Design and implementation of an Information System for Determining the Best Student Graduation Using the Simple Additive Weighting (SAW) Method. The system is designed to determine the best graduates accurately based on several criteria, including report card grades, madrasah assessment scores, UAMNU BK scores, attendance, and achievements. The system was developed using PHP as the programming language, MySQL as the database management system (DBMS), and XAMPP as the local web server. Based on the testing results using the confusion matrix method, the system achieved an accuracy rate of 100%, indicating that it can correctly classify student graduation results. Therefore, the final calculation produced by the system can be used effectively to determine the best student graduates.